Merytokracja czy „elity odpowiedzialnościowe”? Ewangelicka interpretacja zagadnienia elit społecznych - Kopiec, Piotr (Annales. Etyka w Życiu Gospodarczym, 2015)
The notion of meritocracy is among the keywords used in order to describe the contemporary world. It has become more and more an inherent concept of an order whose main factors are said to be globalization as well as the impact of free market philosophy on society and culture. The concept of meritocracy considers the nature of elites. On the one hand, meritocratic elites are taken from groups selected for their merits and competences, but on the other hand they avoid their responsibility towards society and culture. Amongst many counterproposals it seems worthwhile to present the evangelical concept of elites which is deeply embedded in evangelical social teaching. Evangelical theology introduces in its social discourse the notion of the responsibility elites. According to evangelical theologians, the key task to overcome the growing social, economic and cultural crisis of today may be found in the rehabilitation of the notion of common good. Interpreted from a sociological as well as theological standpoint, responsibility elites play an important role when spreading the concept of the common good. The article presents theological guidelines of evangelical teaching on elites as well as evangelical proposals concerning the issue collating them with the broad diagnosis of the meritocratic elites.